Phytochemical investigation, GC-MS analysis and in vitro antimicrobial activity of Coleus forskohlii (Bangladesh Journal of Pharmacology, 2015)
The aim of this study was to investigate the phytochemical constituents, gas chromatography-mass spectrometry (GC-MS) analysis and antimicrobial activity of Coleus forskohlii. The different solvents such as ethanol, chloroform, acetone and aqueous extracts were identified pharmacologically as important bioactive compounds and their antimicrobial properties were studied. In the phytochemical investigation almost all the ethanol extract of leaf, stem and root having secondary metabolites like alkaloids, flavonoids, tannins, saponins, terpenoids, and steroids. The active constituents of the ethanol extract of C. forskohlii root was studied by GC-MS analysis. According to the antimicrobial results ethanol extract of C. froshkolii root showed highest antibacterial activity compared with stem and leaf. The highest antimicrobial activity was observed against Klebsiella pneumonia (19 mm) and Candida albicans (16 mm) in ethanol extract of root. Among the above extracts of leaf, stem and root, ethanol extract of root having antimicrobial activities due to the presence of phytoconstituents.